Differential immunogenicity of HIV-1 clade C proteins in eliciting CD8+ and CD4+ cell responses. - Ramduth, D; Chetty, P; Mngquandaniso, N; Nene, N; Harlow, J; Honeyborne, I; Ntumba, N; Gappoo, S; Henry, C; Jeena, P; Addo, M; Altfeld, M; et al. (2005)
BACKGROUND: The relative immunogenicity of human immunodeficiency virus type 1 (HIV-1) proteins for CD8+ and CD4+ cell responses has not been defined. METHODS: HIV-1-specific T cell responses were evaluated in 65 chronically HIV-1-infected untreated subjects by interferon- gamma flow cytometry with peptides spanning the clade C consensus sequence. RESULTS: The magnitude of HIV-1-specific CD8+ T cell responses correlated significantly with CD4+ cell responses, but the percentage of CD8+ T cells directed against HIV-1 (median, 2.76%) was always greater than that of CD4+ cells (median, 0.24%). Although CD8+ T cell responses were equally distributed among Gag, Pol, and the regulatory and accessory proteins, Gag was the dominant target for CD4+ cell responses. There was no consistent relationship between virus-specific CD8+ or CD4+ cell response and viral load. However, the median viral load in subjects in whom Gag was the dominant CD8+ T cell target was significantly lower than that in subjects in whom non-Gag proteins were the main target (P=.007). CONCLUSIONS: Gag-specific responses dominate the CD4+ T cell response to HIV, whereas CD8+ T cell responses are broadly distributed, which indicates differential immunogenicity of these cells against HIV-1. The preferential targeting of Gag by CD8+ T cells is associated with enhanced control of viral load.